The coadministration of Lactobacillus probiotic augments the antitumor effect of telmisartan in rats - Ahmed M. El-Baz; Amany A. El-Mahmoudy; Sameh Saber; Marwa T. ElRakaiby (AMB Express)
Abstract Colorectal cancer (CRC) is a prevalent disease with a high mortality rate and is significantly affected by microbial dysbiosis. Recent research suggests that modulation of the gut microbiome can have therapeutic benefits and that Angiotensin-II Type 1 Receptor (AT1R) can stimulate cell growth, angiogenesis, and resistance to apoptosis in various cancers. In this study, the adjunctive administration of Lactobacillus spp. and telmisartan, an AT1R blocker, was explored in the treatment of CRC. The effect of telmisartan and a mixture of probiotic species, Lactobacillus delbrueckii and Lactobacillus fermentum, was assessed on key biomarkers and selected gut microbiota taxa in 1,2-dimethylhydrazine-induced CRC in rats. Angiogenesis, inflammation, and apoptosis were assessed by measuring vascular endothelial growth factor (VEGF), carcinoembryonic antigen (CEA), Interleukin 6 (IL-6), and Annexin V levels, respectively. The relative abundance of selected gut microbial taxa, including Bacteroides spp., Clostridium spp., Clostridium coccoides, Ruminococcus spp., and Lactobacillus spp. was analyzed to determine the change in the microbial composition in the different experimental groups of the animal model. This study demonstrated that the unique combination therapy using a Lactobacillus mixture and telmisartan effectively reduced VEGF and IL-6 levels, indicating decreased angiogenesis and inflammation. Lactobacillus spp. co-administration with telmisartan boosted programmed cell death, reversed dysbiosis, improved histopathological outcomes, and reduced CEA levels. These findings offer a new perspective on the role of Lactobacillus spp. and telmisartan in CRC treatment. Further research on their adjunctive use and therapeutic potential are needed to enhance clinical efficacy.